Immobilizing yeast β-glucan on zinc-layered hydroxide nanoparticle improves innate immune response in fish leukocytes. Issue 82 (November 2018) - Velazquez-Carriles, Carlos; Macias-Rodríguez, Maria Esther; Carbajal-Arizaga, Gregorio G.; Silva-Jara, Jorge; Angulo, Carlos; Reyes-Becerril, Martha
Abstract: Nanoparticle-based delivery technologies have played a central role in a wide variety of applications, including cell therapy, gene transformation, and cellular delivery of molecular dyes. This work synthesized via ionic exchange a nanoparticle consisting of zinc-layered hydroxychloride coupled with yeast β-glucan (ZG), whose cellular immune response was evaluated using fish spleen leukocytes. Leukocytes from the marine Pacific red snapper ( Lutjanus peru ) were stimulated with zinc-layered hydroxychloride (ZHC) coupled with yeast β-glucan (GLU) and challenged with live Vibrio parahaemolyticus after 24 h. Structural characterization of this yeast glucan by proton nuclear magnetic resonance (NMR) indicated structures containing (1–6)-branched (1–3)-β-D-glucan. The ZHC and ZG were characterized with X-ray diffraction, infrared spectroscopy, scanning electron microscopy and thermogravimetric analysis. The results of the immunological study showed that ZHC, GLU or ZG were safe for leukocytes because cell viability was higher than 80% compared with DMSO or V. parahaemolyticus exposure. The ZG or GLU treatments enhanced nitric oxide production, superoxide dismutase, catalase and peroxidase activities. Induction of anti- and pro-inflammatory cytokine (IL-1β, IL-6, IL-8, IL-10, IL-12 and IL-17) genes was more pronounced in ZG or GLU treatments compared to the other groups. Based on the results, ZHC nanoparticles can be used as a delivery carrier of yeast β-glucan for enhancing immunity in fish and have great potential application in the aquaculture industry. Highlights: Nanoparticle of zinc-layered hydroxychloride coupled with yeast β-glucan (ZG) was synthesized. ZHC, G and ZG were safe because leukocyte viability was up to 80%. ZG-stimulated leukocytes enhanced NO production and antioxidant enzymatic activities upon Vibrio parahaemolyticus challenge. Anti- and pro-inflammatory cytokine gene expressions regulated differentially in ZHC, G and ZG treatments. ZHC could serves as delivery carrier of yeast β-glucan to enhance fish immunity.